Socioeconomic inequalities in the access to and quality of health care services - Bruno Pereira Nunes; Elaine Thumé; Elaine Tomasi; Suele Manjourany Silva Duro; Luiz Augusto Facchini (Universidade de São Paulo, 2014)
OBJECTIVE To assess the inequalities in access, utilization, and quality of health care services according to the socioeconomic status. METHODS This population-based cross-sectional study evaluated 2,927 individuals aged ≥ 20 years living in Pelotas, RS, Southern Brazil, in 2012. The associations between socioeconomic indicators and the following outcomes were evaluated: lack of access to health services, utilization of services, waiting period (in days) for assistance, and waiting time (in hours) in lines. We used Poisson regression for the crude and adjusted analyses. RESULTS The lack of access to health services was reported by 6.5% of the individuals who sought health care. The prevalence of use of health care services in the 30 days prior to the interview was 29.3%. Of these, 26.4% waited five days or more to receive care and 32.1% waited at least an hour in lines. Approximately 50.0% of the health care services were funded through the Unified Health System. The use of health care services was similar across socioeconomic groups. The lack of access to health care services and waiting time in lines were higher among individuals of lower economic status, even after adjusting for health care needs. The waiting period to receive care was higher among those with higher socioeconomic status. CONCLUSIONS Although no differences were observed in the use of health care services across socioeconomic groups, inequalities were evident in the access to and quality of these services.